Impact of health-related habits on neurodevelopment and mental health in children and adolescents: Impacto de los hábitos relacionados con la salud en el neurodesarrollo y la salud mental en niños, niñas y adolescentes - Bonilla-Flores, Yuly-Yohana; Peña-Parada, Vivian; Cárdenas-Malpica, Paola; Calderon- Balseca, Angie; Fernández-Delgado, Marlen-Karina; Forgiony-Santos, Jesús (Gaceta Médica de Caracas, 2026)
Background: Lifestyles during childhood and adolescence play a critical role in neurodevelopment and mental health, as the developing brain is particularly sensitive to environmental and behavioral factors. Habits related to nutrition, physical activity, and electronic device use influence cognitive, emotional, and social functioning. Objective: This study aimed to analyze scientific evidence on the effects of dietary habits, screen time, and physical activity on neurodevelopment and mental health in children and adolescents. Material and methods: A narrative literature review was conducted using scientific publications from the last five years. Observational, longitudinal, and clinical studies, as well as national and international narrative and systematic reviews, were identified through database searches.